Botulinum toxin type A for the treatment of limb myokymia: Experiences of three children - Sedat Isikay (Annals of Indian Academy of Neurology, 2022)
Myokymia is a rare neuromuscular disorder and limb involvement is not common in this disease. To the best of our knowledge, isolated peroneus longus muscle myokymia was not reported before in the literature; and for that reason treatment protocols were not established. Botulinum toxin type A (BoNT-A), which is used in the treatment of a variety of neurologic disorders, was also defined as a treatment option in myokymia. Herein, we will report three cases of peroneus longus muscle myokymia in children in the absence of any other neurological findings, and the successful results of treatment with local BoNT-A injections. BoNT-A is a safe and effective treatment in myokymia when administered by an experienced clinician and should always be considered when the disorder is persistent and affecting the life of the patient.